Validity of Phydeopale (Physics Video of Patil Lele) Media to Train Critical Thinking Skills of High School Students on Momentum and Impulse Material - Syah, Yoga Pramudya Ferdian; Anggaryani, Mita (Universitas Negeri Surabaya, 2025)
The development of science and technology that is increasingly advanced can support the learning process through the utilization of learning media, one of which is an interactive learning video. The integration of technology into learning activities can encourage the successful development of 21st century skills. This study aims to develop an interactive learning video on momentum and impulse material which is declared valid. The novelty of this research is the use of patil lele traditional game in learning physics on momentum and impulse material which is different from previous research. This research used the Research and Development method with the ADDIE development model. The implementation used One Group Pretest-Posttest and was tested on a limited basis in class XI Science 2 SMA Labschool Unesa 1. The data collection technique used a validation sheet. Media validation was reviewed from ten aspects, namely content, structure, visual, audio, interactivity, duration, creativity, use of technology, ethnophysics, and language. The data analysis technique used was percentage calculation with percentage validation eligibility criteria ≥ 61%. The validators consisted of two physics education lecturers at Surabaya State University and one physics teacher at Labschool Unesa 1 High School. Based on the results of the development research, the average percentage of media validation results was 92% with a very valid category. So that the interactive physics learning video developed is declared feasible to use as physics learning media to train the critical thinking skills of high school students on momentum and impulse material.